2016
DOI: 10.1002/cssc.201600890
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalytic Effect of ZrO2 and α‐Fe2O3 Nanoparticles on BiVO4 Photoanodes for Enhanced Photoelectrochemical Water Splitting

Abstract: Photoelectrochemical water splitting with metal oxide semiconductors offers a cost-competitive alternative for the generation of solar fuels. Most of the materials studied so far suffer from poor charge-transfer kinetics at the semiconductor/liquid interface, making compulsory the use of catalytic layers to overcome the large overpotentials required for the water oxidation reaction. Herein, we report a very soft electrolytic synthesis deposition method, which allows remarkably enhanced water oxidation kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…XRD diffraction pattern of the sample shown in Figure b shows the characteristic peaks of hematite phase (α‐Fe 2 O 3 ) crystals, together with FTO peaks from the substrate which are labeled with an asterisk, confirming the formation of hematite after electrodeposition . The electrode shows to be very active for the oxidation of water under basic conditions (1 M KOH) as reported previously (see Figure SI1) . Films are relatively flat with some texture that provides photocurrent of oxygen evolution under illumination conditions of 300 μA/cm 2 at 0.4 V vs Ag/AgCl.…”
Section: Resultssupporting
confidence: 71%
“…XRD diffraction pattern of the sample shown in Figure b shows the characteristic peaks of hematite phase (α‐Fe 2 O 3 ) crystals, together with FTO peaks from the substrate which are labeled with an asterisk, confirming the formation of hematite after electrodeposition . The electrode shows to be very active for the oxidation of water under basic conditions (1 M KOH) as reported previously (see Figure SI1) . Films are relatively flat with some texture that provides photocurrent of oxygen evolution under illumination conditions of 300 μA/cm 2 at 0.4 V vs Ag/AgCl.…”
Section: Resultssupporting
confidence: 71%
“…Thin‐film hematite electrodes were prepared by a simple and cost‐efficient electrodeposition method, based on a description by Shaddad et al., but with varying calcination conditions as in Refs. .…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that electrochemical deposition of Fe under specific conditions led to the formation of catalytically active a-Fe 2 O 3 nanoparticles on the surface of a water splitting photoanode. 38 Although a-Fe 2 O 3 has been widely studied as a water oxidation photoanode, [39][40][41][42][43] it has been suggested that electrodeposited a-Fe 2 O 3 particles provide cooperative electrocatalytic behavior on BiVO 4 photoanodes for water oxidation. 38 Three different deposition charges of Fe were tested: 5, 12 and 25 mC cm À2 , corresponding to 0.49, 1.06 and 6.27 at% of Fe detected by EDS analysis on Ni foil (ESI, † Fig.…”
Section: Resultsmentioning
confidence: 99%